2021
DOI: 10.1186/s12929-020-00697-0
|View full text |Cite|
|
Sign up to set email alerts
|

CircNOL10 suppresses breast cancer progression by sponging miR-767-5p to regulate SOCS2/JAK/STAT signaling

Abstract: Background Circular RNAs (circRNAs) have caught increasing attentions and interests for their important involvement in cancer initiation and progression. This study aims to investigate the biological functions of circNOL10 and its potential molecular mechanisms in breast cancer (BC). Materials and methods qRT-PCR and western blot assays were performed to measure the expression of related genes. CCK-8, colony formation, flow cytomerty and transwell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…Wang F et al . reported that high-level circNOL10 inhibits BC cell proliferation, migration and invasion in vitro [ 21 ]. This supports that high- or low-level circRNA can affect BC development.…”
Section: Discussionmentioning
confidence: 99%
“…Wang F et al . reported that high-level circNOL10 inhibits BC cell proliferation, migration and invasion in vitro [ 21 ]. This supports that high- or low-level circRNA can affect BC development.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have also indicated that circ-NOL10 is expressed at low levels in breast, lung, and colorectal cancer. 28 , 29 , 30 This agreement suggests that circ-NOL10 is a common player in carcinogenesis. Investigation in lung cancer also found that circ-NOL10 is regulated by the splicing factor ESRP1 .…”
Section: Discussionmentioning
confidence: 69%
“…It is well established that JAK-STAT signaling is involved in breast cancer cell proliferation, metastasis, and chemotherapeutic sensitiveness. For instance, Wang et al reported that CircNOL10 suppressed breast cancer progression by sponging miR-767-5p to regulate SOCS2/JAK/STAT signaling ( Wang et al, 2021 ). Several studies found that JAK-STAT signaling was involved in the chemotherapeutic and endocrine therapeutic resistance in breast cancer ( Lui et al, 2017 ; Zhu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%